Rasionalitas Mahasiswa Disabilitas Tuna Daksa Universitas Negeri Surabaya Memilih Melanjutkan Pendidikan Tinggi - Chariro, Naimatul; Pribadi, Farid (Paradigma, 2024)
Young people with disabilities also have the right to education. Because, the state's goal to educate the nation's children must be accessible to everyone. Thus, the openness of higher education to accept students with disabilities is a strategy for the success of this goal. However, even in the realm of higher education, discrimination against people with disabilities still often occurs, including students with physical disabilities. These students experience exclusion from non-disabled students, difficulty accessing off-campus environments, and many other problems. Therefore, this research wants to examine the rationality of disabled students choosing to continue their higher education at UNESA. By using the analytical knife of Max Weber's theory of social action. Anak muda penyandang disabilitas juga berhak mendapatkan pendidikan. Sebab, tujuan negara untuk mencerdasarkan anak bangsa harus dapat diakses oleh siapa saja. Sehingga, keterbukaan pendidikan tinggi untuk menerima mahasiswa penyandang disabilitas adalah strategi keberhasilan tujuan tersebut. Namun, meski di ranah perguruan tinggi, diskriminasi terhadap penyandang disabilitas masih sering terjadi, tidak terkecuali pada mahasiswa penyandang disabilitas tuna daksa. Mahasiswa ini mengalami pengucilan dari mahasiswa nondisabilitas, kesulitas mengakses lingkungan luar kampus, dan banyak persoalan lain. Oleh sebab itu, penelitian ini ingin mengkaji rasionalitas mahasiswa disabilitas tuna daksa memilih melanjutkan pendidikan tinggi di UNESA. Dengan menggunakan pisau analisis teori tindakan sosial Max Weber. Keywords: Rationality; Disability; Physically disabled; UNESA